Pengarah Citra Kota Malang sebagai Kota Kolonial melalui Metode Serial Vision - Yesaya Moses Rondonuwu; Erlina Laksmiani Wahjutami (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2024)
Title: Directing the Image of Malang City as a Colonial City using the Serial Vision Method Malang City has the potential for buildings representing it as a colonial city. Thomas Karsten was appointed as the planner and designer of Malang City. Urban planning and design results can be felt in the Bouwplan phase from 1917 to 1935. In contrast, Malang City already has elements of images of the city that form an urban image. The research aims to see whether the image of Malang City as a colonial city in the past is still visible today. The research seeks to rediscover traces of the colonial city through serial vision techniques with a synchronic view of the present. The method applied in the research is descriptive qualitative with synchronic data analysis. The data collection technique uses the serial vision method. The research was conducted in 2022 before the current traffic lane changes. From today's perspective, the traces of the colonial city are still quite strong, and the presence of the urban component is still visible through continuous vision. The results of serial vision observations show the elements that form the city's image. Even though the city image theory was put forward by Kevin Lynch in 1960, based on serial vision method tracking data obtained from observations in 2023, Thomas Kasten seems to have been able to think about this for a long time so that the results of his design formed the image of a colonial city.